2009
DOI: 10.1161/circulationaha.108.829176
|View full text |Cite
|
Sign up to set email alerts
|

Trends in All-Cause and Cardiovascular Disease Mortality Among Women and Men With and Without Diabetes Mellitus in the Framingham Heart Study, 1950 to 2005

Abstract: Background-Despite population declines in all-cause mortality, women with diabetes mellitus may have experienced an increase in mortality rates compared with men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

23
381
4
10

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 544 publications
(418 citation statements)
references
References 22 publications
23
381
4
10
Order By: Relevance
“…Our findings are consistent with results from the Framingham Heart Study [5] demonstrating no reduction of mortality rates in diabetes patients over the last 50 years and a persistent twofold higher mortality rate.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings are consistent with results from the Framingham Heart Study [5] demonstrating no reduction of mortality rates in diabetes patients over the last 50 years and a persistent twofold higher mortality rate.…”
Section: Discussionsupporting
confidence: 92%
“…A decline in all-cause and cardiovascular mortality rates has been observed over the last decades among diabetes patients and individuals without diabetes. However, the decline in mortality rates in diabetes patients appears to be markedly lower than in individuals without diabetes [5,6]. Thus, diabetes patients remain at high risk of allcause and cardiovascular mortality [5].…”
mentioning
confidence: 99%
“…Moreover, rates of diabetes‐related complications have declined in the past 2 decades 10, 11. Although mortality rates in patients with diabetes remain higher compared to those without diabetes, reductions in all‐cause mortality in individuals with diabetes have occurred over time throughout the world 12, 13, 14, 15, 16. Therefore, we aimed to examine whether there were improved outcomes over time in individuals with diabetes in the 1999 to 2010 US NHANES.…”
Section: Introductionmentioning
confidence: 99%
“…1, 2 The presence of increased adiposity is associated with elevated risk of development of cardiovascular and renal complications. [2][3][4] Evidence from several studies indicates that obesity and weight gain are associated with an increased risk of hypertension and diabetes. 1,2,5,6 Furthermore, several large cohort studies have demonstrated close associations between obesity, especially abdominal obesity and the onset of chronic kidney disease (CKD) [7][8][9][10][11] and faster CKD progression.…”
Section: Introductionmentioning
confidence: 99%